2005
DOI: 10.1158/1055-9965.epi-05-0034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Direct Mail as a Population-Based Strategy to Increase Mammography Use among Low-Income Underinsured Women Ages 40 to 64 Years

Abstract: Women with inadequate health insurance have lower mammography rates than the general population. Finding successful strategies to enroll eligible women is an ongoing challenge for the National Breast and Cervical Cancer Early Detection Program. To test the effectiveness of a population-based strategy to increase mammography utilization among lowincome underinsured women ages 40 to 64 years, a randomized trial was conducted to assess the effect of two mailed interventions on mammography utilization through Sage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…Unique among NBCCEDPs, Sage has a call center staffed by patient navigators (see Freund et al, 2008) who are fluent in English and other languages relevant for Sage’s target population. More details on NBCCEDPs (Lee et al, 2014) and Sage have been published elsewhere (Slater et al, 2005). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unique among NBCCEDPs, Sage has a call center staffed by patient navigators (see Freund et al, 2008) who are fluent in English and other languages relevant for Sage’s target population. More details on NBCCEDPs (Lee et al, 2014) and Sage have been published elsewhere (Slater et al, 2005). …”
Section: Methodsmentioning
confidence: 99%
“…497–498). Financial incentives have been shown to increase health-enhancing behaviors (e.g., Gneezy, Meier, & Rey-Biel, 2011; Slater et al, 2005), and low-income smokers tend to be responsive to incentives (Bryant et al, 2011). However, incentives tend to be effective for encouraging preventive care that requires only a single activity or simple behavior but not complex actions that require additional engagement beyond initial intervention services (see Kane, Johnson, Town, & Butler, 2004).…”
mentioning
confidence: 99%
“…However, it did not have a significant impact on their behaviour (Carre et al, 2008). A US study investigating the effects of direct mail to increase mammography use showed that after 1 year the intervention group had significantly higher participation rates than the controls (Slater et al, 2005).…”
Section: Mailout Effectiveness As a Health Promotion Strategymentioning
confidence: 99%
“…To give a slightly more detailed feel for a typical study in this area, Slater et al (2005) randomly administered two types of mail based inter ventions to encourage low income U.S. women aged forty to sixty four years to undergo mammography. Both of the interventions offered a free mammogram if the subjects called a toll free number, with one inter vention also offering a small financial incentive of $10 if they actually underwent the mammogram within one year.…”
Section: User Financial Incentivesmentioning
confidence: 99%